Pemanfaatan Teknologi dalam Meningkatkan Kemampuan Sumber Daya Manusia Lembaga Pendidikan Tajaul Karomah Desa Situgadung Kabupaten Tangerang - Nelsi, Mitri; Akbar, Irfan Rizka; Sabina, Fitri (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The rapid development of information and communication technology has significantly influenced the education sector, requiring educational institutions to enhance the competence of their human resources in utilizing technology effectively. This community service activity (PKM) aims to improve the technological skills of teachers and students at the Tajaul Karomah Educational Institution in Situgadung Village, Tangerang Regency. The PKM was conducted on May 3–4, 2025, by a team of 15 lecturers from Pamulang University, involving 45 participants consisting of teachers and students. The implementation method consisted of three stages: preparation, execution, and reporting. During the execution stage, participants engaged in a series of activities including material presentations, practical sessions, discussions, and Q&A. The materials delivered focused on the use of digital tools for teaching and learning, basic digital literacy, and the integration of technology in classroom activities. The results of the activity showed a significant increase in participants' understanding and confidence in using digital technology for educational purposes. Feedback from participants indicated high levels of satisfaction and a desire for continued training. This PKM program successfully contributed to empowering the human resources of the Tajaul Karomah Educational Institution to be more adaptive and responsive to technological advancements in education.